Comparative Evaluation of Volatile Profiles of Asian Hard Clams (Meretrix meretrix) with Different Shell Colors by Electronic Nose and GC-MS. Issue 1 (2nd January 2021) - Wen, Xinyi; Chen, Aihua; Xu, Yanshun; Wu, Yangping; Yang, Yunyi; Zhang, Yu; Cao, Yi; Chen, Suhua
ABSTRACT: Odor is an important factor influencing the acceptance of clams by the consumer. In order to better understand the flavor characteristics of different clams, the volatiles in raw and cooked Meretrix meretrix with three shell colors (mottled shell, red shell, and yellow shell) were investigated by electronic nose and gas chromatography-mass spectrometry (GC-MS). A total of 69 volatiles, dominated by alcohols (32.10–41.02%) and 25 odor-active compounds, were identified in the raw samples, while 73 volatiles, dominated by aldehydes (55.18–58.22%) and 27 odor-active compounds, were determined in the cooked samples. Compared to raw samples, cooked samples had higher concentrations and odor activity values (OAVs) of volatiles. Among the raw clams, OAVs of volatiles in red shell clams were significantly higher than yellow shell clams. According to both electronic nose and GC-MS, all the samples could be distinguished, and 3-octanone, (Z)-1, 5-octadien-3-ol, linalool, 1-octen-3-one, 1-octen-3-ol, 2-nonanone, (E, E)-2, 4-heptadienal, and undecanal were the key volatiles to distinguish the odor profile of Meretrix meretrix with different shell colors.